Wi-Fi Jamming Tool With NodeMCU (v.3 Lolin board) ESP8266 Deauther Microcontroller Based - Afif Khairullah; Agung Susilo Yuda Irawan; Didi Juardi (Peneliti.net, 2022)
National cyber security is one area that needs to be encouraged and strengthened by the government as an effort to increase economic growth and realize national security because of the rise of crimes that use technology for things that are certainly detrimental to Indonesian security. Therefore, the author has designed and realized a device that can detect and disrupt Wi-Fi signals which are considered problematic and disrupt the course of state activities. This device uses the NodeMCU tool (board v.3 Lolin) ESP8266, this tool will later function for access to Wi-Fi. This tool will later read and provide Wi-Fi information around it which will then display the results on the cellphone or laptop of the owner of the device. Based on the test results, this tool is able to detect Wi-Fi signals with a distance of approximately 100 meters and is able to connect properly